Keratinocytes use FPR2 to detect Staphylococcus aureus and initiate antimicrobial skin defense - Lebtig, Marco; Scheurer, Jasmin; Muenkel, Marie; Becker, Janna; Bastounis, Effie; Peschel, Andreas; Kretschmer, Dorothee (Frontiers in Immunology, 2023)
Keratinocytes form a multilayer barrier that protects the skin from invaders or injuries. The barrier function of keratinocytes is in part mediated by the production of inflammatory modulators that promote immune responses and wound healing. Skin commensals and pathogens such as Staphylococcus aureus secrete high amounts of phenol-soluble modulin (PSM) peptides, agonists of Formyl-peptide receptor 2 (FPR2). FPR2 is crucial for the recruitment of neutrophils to the sites of infection, and it can influence inflammation. FPR1 and FPR2 are also expressed by keratinocytes but the consequences of FPR activation in skin cells have remain unknown. Since an inflammatory environment influences S. aureus colonization, e. g., in patients with atopic dermatitis (AD), we hypothesized that interference with FPRs may alter keratinocyte-induced inflammation, proliferation, and bacterial colonization of the skin. To assess this hypothesis, we investigated the effects of FPR activation and inhibition in keratinocytes with respect to chemokine and cytokine release as well as proliferation and skin wound gap closure. We observed that FPR activation induces the release of IL-8, IL-1 and promotes keratinocyte proliferation in an FPR-dependent manner. To elucidate the consequence of FPR modulation on skin colonization, we used an AD-simulating S. aureus skin colonization mouse model using wild-type (WT) or Fpr2-/- mice and demonstrate that inflammation enhances the eradication of S. aureus from the skin in a FPR2-dependent way. Consistently, inhibition of FPR2 in the mouse model or in human keratinocytes as well as human skin explants promoted S. aureus colonization. Our data indicate that FPR2 ligands promote inflammation and keratinocyte proliferation in a FPR2-dependent manner, which is necessary for eliminating S. aureus during skin colonization.